2001
DOI: 10.1097/00007632-200108010-00013
|View full text |Cite
|
Sign up to set email alerts
|

Implementation Barriers for General Practice Guidelines on Low Back Pain

Abstract: Improvement of the quality of back pain care may still be possible. Implementation strategies should aim at training physicians in communication skills, especially about subjects for debate, where patients' beliefs and experiences color their expectations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
121
2
4

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 152 publications
(133 citation statements)
references
References 18 publications
1
121
2
4
Order By: Relevance
“…An important aim of the Norwegian campaign was to improve the general public's knowledge, attitudes, and beliefs about LBP in order to create a better climate for healthcare providers to give care in accordance with evidence-based guidelines. Patients' expectancies have previously been listed as one of many barriers to professionals' adherence to guidelines [18,19]. However, even though LBP beliefs appear to have improved in the general public, we did not see decreased LBP-related absence from work following the campaign [12].…”
Section: Intervention Countiescontrasting
confidence: 66%
“…An important aim of the Norwegian campaign was to improve the general public's knowledge, attitudes, and beliefs about LBP in order to create a better climate for healthcare providers to give care in accordance with evidence-based guidelines. Patients' expectancies have previously been listed as one of many barriers to professionals' adherence to guidelines [18,19]. However, even though LBP beliefs appear to have improved in the general public, we did not see decreased LBP-related absence from work following the campaign [12].…”
Section: Intervention Countiescontrasting
confidence: 66%
“…The reason for these exclusions was the belief that the authors' findings were not consistent with or reflective of the data presented. The remaining 12 studies were published between 1998 and 2006, [25][26][27][28][29][30][31][32][33][34][35][36] and were all published in English (Supplementary Table 2). Five of the studies were from the UK, while the remaining seven were from the US, Canada, and the Netherlands.…”
Section: Resultsmentioning
confidence: 99%
“…[24][25][26][27][28][29][30][31][32][33][34][35] Studies indicated that some GPs were sceptical about the evidence…”
Section: Questioning the Guidelinesmentioning
confidence: 99%
“…A combination of approaches appears to be the most effective way to achieve lasting change (Grol and Grimshaw, 1999). Implementation can only be effective if it tackles obstacles such as disagreement with the content of the new care model, doubts about its feasibility in daily practice and reluctance from colleagues (Grol, 1997;Schers et al, 2001). Furthermore, organisational adjustments (i.e., creating organisational and structural conditions, restructuring the care processes, changing tasks, providing resources and support) may be necessary to maintain the change (Grol and Grimshaw, 1999).…”
Section: Introductionmentioning
confidence: 99%